Endoscopic Excision of A Fibroadenoma Breast: Trans Axillary Approach - Adhikary, S; Sood, S; Dunghel, K; Rajbanshi, S; Shakya, V; Kaniya, S (Kathmandu University Medical Journal, 2013)
Benign breast lumps affect 10% of females in their lifetime. Surveillance, assurance, medications and surgical excision are options available to surgeons. Avoiding scars on the breast is an inherent feminine desire. Numerous minimal invasive approaches have evolved due to this concern. The time honoured circumareolar incisions camouflages the scar to a large extent, yet the incision still remains on the breast tissue and unfortunately the scar undergoes the same old sequelae as with any other scars both aesthetically or psychosocially. The close by anatomical space; axilla provides an easy access for endoscopic breast surgery. We utilized this area and applied our expertise to remove a fibroadenoma in a teenager which spared her breast from the scar. The technique was safe and effective. It conserved aesthetics and led to a better compliance. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 106-108 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7357